Can the rotation of chief accountants improve the accounting information quality of state-owned enterprises? - Jian Chu (China Journal of Accounting Studies (CJAS), 2023)
This paper attempts to study the effect of the rotation of chief accountants of central SOEs. It is found that the rotation of chief accountants can improve the accounting information quality of SOEs. Mechanism analyses indicate that the above result is weakened when the tenure of chief accountants is long or after central SOEs carry out the pilot of establishing a standardised board or are audited by the National Audit Office. When further considering the types of rotation, the above result is only reflected when chief accountants come from SOEs in different industries or different cities or chief accountants are promoted. Economic consequence analyses indicate that the rotation of chief accountants alleviates the problem of over-investment and excess perks in SOEs by improving accounting information quality. In summary, the rotation of chief accountants can enhance their independence to improve the governance of SOEs and prevent the loss of state-owned assets.
Keywords: 650; Chief accountants; financial management and supervision; independence; rotation; state-owned enterprises